DEVELOPMENT OF INTERACTIVE MULTIMEDIA IN IMPROVING STUDENTS' DIGITAL LITERACY SKILLS - Rochman, Fatkhur; Hunaifi,, Abdul Aziz; Santi, Novi Nitya (Universitas Labuhanbatu, 2024)
The background of this research was carried out by means of classroom observations and interviews with teachers and students. Based on the results of interviews and observations obtained data that the use of teaching materials such as learning media is still lacking. Teaching materials that are often used are textbooks and blackboards. The solution to overcome the problem is to develop learning media, namely smart apps Creator. The aims of the study were: (1) to determine the validity of interactive multimedia, (2) to determine the practicality of interactive multimedia, (3) to determine the effectiveness of interactive multimedia. This research is a type of development research (R&D) using the Borg and Gall development model through 10 stages (1) research and data collection, (2) planning, (3) product draft development, (4) initial field trials, (5) revision design, (6) field trials, (7) product improvement, (8) trial use, (9) final product improvement, (10) dissemination and implementation.The Borg and Gall stage is used to analyze and find out the needs at school. This stage is to determine and design the product to be developed. The Development stage of the final product is different from other products. The disseminate stage is used for the product dissemination process through validation. The conclusion of this study: Interactive multimedia is said to be very valid with a percentage of 85%. The results of the response of the learning media teacher are said to be very practical with a percentage of 86%. Interactive Multimedia. said to be very effective because after a limited trial it got a percentage of 86% and an extensive trial got 85%.